The farm laborer - Morgan, Edward Allen (My University, 1907)
Introduction: A farm laborer in this country is a person who works on a farm for hire, and he is not a person who has a tenant proprietorship in a farm. He is one of the necessary beings that is becoming so scarce on our farms today. It is he who is now puzzling the minds of our farmers all over this broad land. The farm laborer problem has become a difficult problem to solve. Why is it? The question naturally arises; Is it because the farm hand does not receive steady employment? Are the working hours too long or the wages too low? Or is the treatment received from his employer not satisfactory? The writer will try and solve this problem by a series of illustrations together with a recitation of his experience as a farm laborer. It is a very general admitted fact today that one great check upon successful farming at the present time is the want of steady,competent and reliable help. Many who have invested their capital in lands and stock have gone out of the farming business because reliable help could not be obtained; and others have for the same reason deterred from entering upon agricultural pursuits. The problem of securing good help on the farm is growing worse every year. But in some localities, especially where the foreign element prevails, many farmers are fortunate in being blessed with large families, the greater part of the work being done by the farmer himself with the help of his good wife and children. However, in the western Kansas wheat belt there are seasons of the year when it becomes necessary to hire additional help to take care of the great crop, and many laborers from the corn belt further east travel westward to assist in harvesting the crop. But his work lasts only a short time, while the expenses of getting…
Citation: Morgan, Edward Allen. The farm laborer. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Agriculture; Agriculture in the United States; Farm Laborers; Theses